The scales of black holes with nAdS2 geometry - Junho Hong; Finn Larsen; James T. Liu (Journal of High Energy Physics, 2019)
Abstract We study nearly extreme black holes with nearly AdS2 horizon geometry in various settings inspired by string theory. Our focus is on the scales of the nAdS2 region and their relation to microscopic theory. These scales are determined by a generalization of the attractor mechanism for extremal black holes and realized geometrically as the normal derivatives along the extremal attractor flow. In some cases the scales are equivalently determined by the charge dependence of the extremal attractor by itself. Our examples include near extreme black holes in D ≥ 4 dimensions, AdS boundary conditions, rotation, and 5D black holes on the non-BPS branch.